Dominance style is a key predictor of vocal use and evolution across nonhuman primates. Issue 7 (28th July 2021) - Kavanagh, Eithne; Street, Sally E.; Angwela, Felix O.; Bergman, Thore J.; Blaszczyk, Maryjka B.; Bolt, Laura M.; Briseño-Jaramillo, Margarita; Brown, Michelle; Chen-Kraus, Chloe; Clay, Zanna; Coye, Camille; Thompson, Melissa Emery; et al.
Abstract : Animal communication has long been thought to be subject to pressures and constraints associated with social relationships. However, our understanding of how the nature and quality of social relationships relates to the use and evolution of communication is limited by a lack of directly comparable methods across multiple levels of analysis. Here, we analysed observational data from 111 wild groups belonging to 26 non-human primate species, to test how vocal communication relates to dominance style (the strictness with which a dominance hierarchy is enforced, ranging from 'despotic' to 'tolerant'). At the individual-level, we found that dominant individuals who were more tolerant vocalized at a higher rate than their despotic counterparts. This indicates that tolerance within a relationship may place pressure on the dominant partner to communicate more during social interactions. At the species-level, however, despotic species exhibited a larger repertoire of hierarchy-related vocalizations than their tolerant counterparts. Findings suggest primate signals are used and evolve in tandem with the nature of interactions that characterize individuals' social relationships.